Carpal Tunnel Syndrome Secondary to Fibrolipomatous Hamartoma of the Median Nerve - Michel, Christopher R (Cureus, 2021)
Fibrolipomatous hamartoma (FLH) is a rare, benign neoplasm that affects the median nerve predominantly and can present with compressive symptoms. MRI can be used to diagnose this condition without the need for a nerve biopsy. While no definitive treatment has been described, open carpal tunnel release for nerve decompression is currently the standard of care to alleviate compressive neuropathies of the median nerve. In this report, we describe a case of FLH diagnosed via MRI in which the patient’s symptoms responded to open carpal tunnel release.